A new ent-kaurane diterpene from Euphorbia stracheyi Boiss. Issue 2 (17th January 2017) - Liu, Tie; Liang, Qian; Xiong, Na-Na; Dai, Lin-Feng; Wang, Jun-Ming; Ji, Xiao-Hui; Xu, Wen-Hui
Abstract: The chemical investigation of whole plants Euphorbia stracheyi Boiss from China led to the isolation of one new ent -kaurane diterpene, ent -Kaurane-16 β, 17, 19-triol-3-one (1 ), along with three known ent -kaurane diterpenoids (2 –4 ) as ent -Kaurane-3 α, 16 β, 17-triol (2 )， ent -16 S, 17-dihydroxy-kaurane-3-one (3 ) and ent -3 S, 16 S, 17-trihydroxy-kaurane-2-one (4 ). Their structures were elucidated by extensive spectroscopic analyses including 1D, 2D NMR, HR-ESI-MS, and by comparison with the literature. Compound2 was a new natural product and firstly isolated from nature, while compounds (3 –4 ) were isolated from E. stracheyi for the first time. All isolated compounds (1 –4 ) were evaluated for their cytotoxic activities against five human cancer cell lines (including A-549, SMMC-7721, HL-60, MCF-7 and SW-480). Graphical Abstract: